Integrating local and scientific ecological knowledge to assess African forest elephant (Loxodonta cyclotis) populations in a data-deficient region, Eastern Democratic Republic of Congo - Leonard K Mubalama; Gedeon T Banswe (Pachyderm)
Given this need to study wildlife populations reliably, quickly and within financial and human resource constraints faced by wildlife managers, we evaluated the pooling local expert opinion (PLEO) as a tool for collecting extensive data on local animal abundance and population trends. We quantified reliability of abundance estimates derived from interviews by comparing them with those obtained from standard field-sampling protocols (distance sampling). We also explored the complementarity of these two approaches in assessing population status and distribution. We estimated there are c. 161 individuals in the selected Itombwe nature reserve and Luama hunting domain landscape covering 1,712 km2. The highly suitable elephant habitat in the Itombwe Reserve was set at 1,045.5 km2 while the largest total of low and unsuitable area was estimated to be 1,529.9 km2. Overall, this study shows that the PLEO methodology provides an effective and complementary tool to estimate forest elephant trend and habitat suitability in tropical rainforests by involving local communities in biodiversity conservation. We suggest that by incorporating the PLEO methodology into regular monitoring activity, conservation bodies can create a platform that allows for participatory wildlife monitoring and create the platform to involve local communities in elephant conservation.